Seroprevalence of Australia antigen (HbsAg) among blood donors in local population - Dr. Mayur J. Kokani; Dr Chiragkumar B. Menapara (Tropical Journal of Pathology and Microbiology, 2018)
Introduction:Transfusion of Blood & Blood Components is one of the four recognized modes of Hepatitis B virus infection andHBsAg or Australia Antigen in the serum is the earliest marker of active HBV infection (acute/chronic) being detectable even before elimination of transaminases and onset of clinical illness. Various strategies are being used to reduce this transfusion transmitted infection.Objectives:To determine the Seroprevalence of HBsAg among blood donors in and around Junagadh (Gujarat) and to compare it withthat of other regions in India.Methods:The study was conducted on apparently healthy blood donors over a period of 3 years from January-2015 to December-2017 at Blood Bank, Department of Pathology, GMERS Medical College and Hospital, Junagadh in order to assess the prevalence of hepatitis B virus infection. A total number of 18368 blood donors were included in this study. Both rapid HBsAg card test and HBsAg ELISA test were used for this study purpose.Result:Out of 18368 donors, 14102 (76.77%) were in-house donors and 4266 (23.23%) were outdoor-camp donors. 17346 (94.44%) were males & 1022 (5.56%) were females. Out of 18368 blood units, 487 (2.65%) were discarded and out of them 109 (22.38%) were HBsAg reactive. The Seroprevalence of HBsAg was found to be 0.59%.Conclusion:Blood Donors areoftenfound to be reactive for Australia Antigen and others. In order to reduce this Seroprevalence, more sensitive screening assays and appropriate donor selection are must.